The Forming Surface Layer of the Duplex Cast Steel After Turning - Dyl, T. (Scientific Journal of Gdynia Maritime University, 2018)
The paper presents results of experimental studies of turning cast steel grade GX2CrNiMoCuN25-6-3-3. The aim of the research was to determine the geometry of the cutting edge and the technological parameters of cutting that are conducive to obtaining the roughness in the field of very accurate machining. It can achieve the appropriate technological quality of the workpiece surface. After experimental studies it was determined that there is a reduction of roughness using suitable inserts. Turning were made for the duplex cast steel. The technological parameters of machining process were used: feed rate f = 0.1–0.2 mm/rev, depth of cut ap = 0.5 mm, cutting speed vc = 50–100 m/min. Longitudinal machining was made using universal lathe CDS 500 ´ 1000 equipped with CCMT carbide tipped inserts with CVD coatings.